Evaluating the use of capillary electrophoresis in the forensic DNA profiling of burnt teeth - Geldenhuys, Adriaan (Department of Pathology, 2024)
Fires are a frequent cause of death, both globally and in South Africa, and often, individuals are burnt beyond the point of visual recognition. Teeth maintain their structure and can withstand high temperatures; making them a possible source of DNA from burnt human remains. DNA profiling is the current gold standard in forensic human identification, however, limited literature pertaining to DNA profiling of burnt teeth exists. The aim of this study was thus to evaluate the success of capillary electrophoresis in the forensic DNA profiling of teeth burnt at different temperatures, using an optimised DNA extraction protocol. Tooth samples from 25 donors (n = 100 [4 teeth per donor]) were subjected to three burning conditions, one tooth was left unburnt to act as a control and three teeth were each burnt in a muffle furnace at 100 ˚C, 200 ˚C, and 300 ˚C. The colour and weight of the teeth were recorded before and after burning. DNA was extracted using an optimised demineralisation step. Extracted DNA was quantified through real-time PCR and profiled using capillary electrophoresis with the Promega PowerPlex® ESX 16 system. Teeth burnt at 100 ˚C resulted in the most full profiles (96 % ; n = 24/25), followed by teeth burnt at 200 ˚C (84 %; n = 21/25), with 16 % partial profiles obtained (n = 4/25). Teeth burnt at 300 ˚C resulted in a large number of failed profiles (88 % ; n = 22/25), and had a significant decrease in profiling success (p = 0.001) and concentration (p = 0.001), and were significantly more degraded (p = 0.001), compared to control samples and samples burnt at lower temperatures. These results suggest that conventional DNA profiling methods and the DNA extraction method used herein are suitable for obtaining full DNA profiles from teeth exposed to temperatures as high as 200 ˚C, however, more sensitive methods such as targeted next generation sequencing (NGS) would be recommended to obtain more insight into highly degraded and fragmented samples, such as those burnt at 300 ˚C.